Can Tissue Expansion Reconstruction in the Trunk of Children Increase the Risk of Scoliosis?. Issue 2 (May 2021) - Yen, Paul; Bucevska, Marija; Reilly, Christopher; Verchere, Cynthia
Introduction: We hypothesize that treatment of significant truncal lesions with truncal tissue expanders and subsequent flap surgery in pediatric patients may increase the risk of scoliosis. This study aims to investigate any relationship between tissue expansion (TE) and scoliosis and to compare the prevalence of scoliosis in our tissue expander population to the general population. Methods: Health records of patients who underwent truncal TE at BC Children's Hospital between 1997 and 2017 were retrospectively reviewed and analyzed. The cross-sectional component of the study consisted of radiological imaging to establish the presence or absence of scoliosis. Results: We identified 28 patients who underwent truncal TE over the study period. Ten had a scoliosis X-ray on their chart or as a part of the study. Three (10.7%) patients were identified as having developed scoliosis after TE. Conclusions: We recommend that pediatric TE patients be made aware of the potential complication of scoliosis and be followed closely in the years during and after their treatment, in order to allow for preventative measures, early diagnosis and early management (if required).